The Use of Augmented Reality in Distance Language Learning in Indonesia and Singapore: A Descriptive Study with Survey Methods - Casmat, Memet; Muralitharan, Ali (Metafora: Jurnal Pembelajaran Bahasa Dan Sastra, 2024)
This study aims to describe the use of Augmented Reality for student’s distance learning in Indonesia and Singapore. This study is descriptive research with a survey method. The survey was conducted with 39 student’s distance learning. Data is collected using Google Form questionnaires. Data analysis is carried out by calculating the frequency and is presented as percentages. Participants in this study were chosen randomly for data variation. The presentation of data is carried out qualitatively based on the respondents’ answers to the questions asked. The study participants argued that augmented reality was feasible, even though it was recognized as encountering obstacles. Based on the results of a survey conducted has made AR and VR more viable and desirable in many fields, including education, digital platforms are used to support online learning. The platforms used are WhatsApp and video conferencing, such as Google Meet. Integrating technology is considered important for students to support the learning process. Conscious and planned efforts and student motivation are critical to increasing their experience and skills in utilizing technology in learning.